ON SUBSTANTIATION OF SELECTION OF ECONOMIC AND MATHEMATICAL METHODS FOR THE ASSESSMENT OF ENERGY EFFICIENCY OF PRODUCTION FACILITIES - Bederak, Ya. S. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2017)
Research purpose is generalization and further development of economic- mathematical methods for ensuring energy-efficient operation mode of production facilities. The above methods can be used for selection of the most energy-efficient production lines, mechanisms; pumping, compression, ventilation installations or other electric receivers among several similar ones by using equal and unequal weight criteria. An example of comparing the efficiency of the production facilities of the chemical industry is showed by a priori ranking and morphological (geometric) methods. The method of control the correctness of the production facilities in the case when the electric load depends on two parameters in triangular coordinates in the presence of boundary restrictions is described. The identity of the current energy values calculated by Holt predicted value at a predetermined optimal smoothing constant determines the stability of the process. Expedience of application the autocorrelation coefficient for testing processes on the stability is proved.